Respuesta :
To determine the answer we need to use the slope point form of the equation of the line. It is expressed as:
y - y1 = m(x - x1)
where m is the slope and is (y2-y1) / (x2-x1)
We do as follows:
y - y1 = m(x - x1)
y - -4 = (2+4)/(6-0) (x-0)
y +4 = x
Therefore, the third option is the correct answer. Hope this answers the question.
y - y1 = m(x - x1)
where m is the slope and is (y2-y1) / (x2-x1)
We do as follows:
y - y1 = m(x - x1)
y - -4 = (2+4)/(6-0) (x-0)
y +4 = x
Therefore, the third option is the correct answer. Hope this answers the question.